Wastes from the coal-enrichment process as alternative reducers for lead smelting from lead-acid accmulator scrap - J. Lipart; T. Matuła; M. Niesler; L. Blacha; J. Filipczyk (Metalurgija, 2013)
In the paper, results of the study on a possible utilization of coal-enrichment wastes as alternative reducers for lead smelting from acid-lead accumulator scrap are presented. For the experiments, the following alternative carboniferous reducers were selected: coal slurry, anthracite dust and coal soot. The investigations included both laboratoryscale experiments and semi-industrial tests in a rotary furnace. The findings allowed for a review of the effects of a sample type (loose material or material post a preliminary agglomeration process), loaded into the furnace, on a final process yield.